2018
DOI: 10.1002/adem.201800036
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich Structures with Prismatic and Foam Cores: A Review

Abstract: This article provides a comprehensive review of recent research efforts on the development and characterization of sandwich structures with corrugated, honeycomb, and foam cores. The topics discussed in this review article include aspects of core-face bonding and reinforcement, enhancement of core mechanical properties and panel performance (including the role of structural hierarchy), and multifunctional advantages offered by different core constructions. In addition, the review discusses potential applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 149 publications
(175 reference statements)
0
33
0
1
Order By: Relevance
“…Therefore, good mechanical properties of stitched foam core sandwich structure are guaranteed. Xiong et al 30 summarized the schematic of stitched foam sandwich structure as shown in Figure 9. There are various types of stitched foam cores such as X-core foam core, K-core foam core, vertical stitched foam core, and oblique stitched foam core.…”
Section: Typical Core Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, good mechanical properties of stitched foam core sandwich structure are guaranteed. Xiong et al 30 summarized the schematic of stitched foam sandwich structure as shown in Figure 9. There are various types of stitched foam cores such as X-core foam core, K-core foam core, vertical stitched foam core, and oblique stitched foam core.…”
Section: Typical Core Structuresmentioning
confidence: 99%
“…Caliri et al 29 reviewed theories and solution methods for laminated and sandwich structures. A comprehensive review of recent research efforts on the development and characterization of sandwich structures with corrugated, honeycomb, and foam cores was published by Xiong et al 30 Ahn 6 reviewed research on metallic sandwich plates with periodically repeated metallic inner structures in terms of design, manufacturing, and formability. Nikbakt et al 31 presented a review of optimization studies on composite structures by representing a classification based on the type of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Such structures are made up of a low-density core and facesheets manufactured from high specific strength fiber-reinforced polymers (FRP). Foam cores, honeycombs, or folded cores are the most commonly used [4]. The elements of sandwich structures fulfill specific roles in typical bending applications.…”
Section: Introductionmentioning
confidence: 99%
“…The face sheets are made of metal or composite materials, and lightweight sandwich cores are developed, such as metal foam, honeycomb, and corrugated core . Also, hierarchical lattice, triangular lattice, and pyramidal truss have been developed with the improvement of the manufacturing process. The sandwich structure is widely used in engineering, e.g., aircraft, spacecraft, high‐speed trains, ships, and vehicles.…”
Section: Introductionmentioning
confidence: 99%